GAMBARAN POLA DAN KUALITAS TIDUR IBU MENYUSUI PADA TIGA BULAN PERTAMA DI KECAMATAN LUMBAN JULU KABUPATEN TOBA PROVINSI SUMATERA UTARA - Lichentia Putri Elisabet Panjaitan; Widia Lestari; Riri Novayelinda (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2022)
Breastfeeding is a period of adaptation of mothers after pregnancy and childbirth. This period is a period of adaptation for a mother in changing her sleep patterns and quality. This study aims to describe the pattern and quality of sleep of breastfeeding mothers in the first three months in Lumban Julu District of Toba, North Sumatra Province. This study used a descriptive research design with a quantitative approach. The sample of this study was 85 respondents who were taken using a total sampling technique. The analysis used is univariate analysis. Results: There were 63 respondents (74.1%) with multipara parity. A total of 51 respondents (60%) had poor sleep patterns and 76 respondents (89.4%) had poor sleep quality). Sleep patterns and quality of breastfeeding mothers in the first three months tend to be poor.Keywords: breastfeeding mother, sleep pattern, sleep quality